Histopathological evaluation of prostate specimens after thermal ablation may be confounded by the presence of thermally-fixed cells - Mikael Anttinen; Eemil Yli-Pietilä; Visa Suomi; Pietari Mäkelä; Teija Sainio; Jani Saunavaara; Lauri Eklund; Roberto Blanco Sequeiros; Pekka Taimen; Peter J. Boström (TAYLOR & FRANCIS LTD, 2022)
Purpose: Prostate cancer can be eradicated with heat exposure. However, high and rapid temperature elevations may cause thermofixation giving the appearance of viable tissue. The purpose was to characterize the immunoprofile and evaluate the viability of prostate regions with suspected thermofixation.
Methods and materials: A prospective, ethics-approved and registered study (NCT03350529) enrolled six patients with MRI-visible, biopsy-concordant prostate cancer to undergo lesion-targeted MRI-guided transurethral ultrasound ablation (TULSA) followed by radical prostatectomy at 3 weeks, to evaluate the accuracy and efficacy of TULSA with whole-mount histology as a reference standard. If ambiguity about complete necrosis within the ablated region remained after hematoxylin-eosin staining, viability was assessed by immunohistochemistry. Treatment day MRI-thermometry and 3-week contrast-enhanced MRI post-TULSA were examined to assess ablation success and correlation with histopathology.
Results: One patient presented with an apparently viable subregion inside the ablated area, surrounded by necrosis on H&E staining, located where temperature was highest on MRI-thermometry and tissues completely devascularized on MRI. Immunoprofile of the apparently viable tissue revealed changes in staining patterns suggesting thermofixation; the most significant evidence was the negative cytokeratin 8 staining detected with Cam5.2 antibody. A comprehensive literature review supports these observations of thermofixation with similar findings in prostate and other tissues.
Conclusion: Thermally-fixed cells can sustain morphology on H&E staining. Misinterpretation of treatment failure may occur, if this phenomenon is not recognized and immunohistochemistry performed. Based on the previous literature and the current study, Cam5.2 staining for cytokeratin 8 appears to be a practical and reliable tool for distinguishing thermally-fixed from viable cells.